ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KETERBUKAAN STATUS HIV SEROPOSITIF WANITA PENDERITA HIV/AIDS TERHADAP PASANGAN SEKSUAL DI LSM VICTORY YOGYAKARTA - Rukmi, Dwi Kartika; Darussalam, Miftafu (Media Ilmu Kesehatan, 2018)
Background: The disclosure of womenâs HIV status toward their sexual partners is an important issue that should be regarded as one of the efforts to prevent and control the spread of HIV. Research on the disclosure of seropositive HIV status as well as women-related factors in Indonesia, especially Yogyakarta is only a few. Objective: The purpose of this study is to analyse a factor related to the growth of HIV-positive female HIV/AIDS to sexual partners in LSM Victory Yogyakarta Methods: This is a correlational descriptive research along with its cross-sectional approach on 329 women with HIV/AIDS at the Victory Plus NGO from June to July 2016. This research used a purposive sampling method and a questionnaire as the data collection technique. The bivariate analysis test was undertaken by using a chi square and multivariate test along with a logistic regression. Result: The multivariate analysis and logistic regression show five independent variables related to the disclosure of seropositive HIV status of women with HIV/AIDS toward their sexual partners, namely ethnicity (aOR = 36,859; 95% CI; (6,544-207,616)) religion (aOR =0,255; 95%CI; (0,075-0,868)), discussion with partners prior to the HIV test (aOR =0,069; 95%CI; (0,065-0,438)) , types of sexual partners (aOR = 0.191; 95% CI; (0.082-0,445)) and knowledge on the partnersâ HIV status (aOR = 0.036; 95% CI; (0.008-0.160)). The highest level of reason for seropositive HIV women not to be open about their partnersâ status is the fear of being rejected by their partners and the environmental stigma of HIV AIDS disease. Conclusion: The disclosure of seropositive HIV status in women with HIV/AIDS in the Victory Plus NGO of Yogyakarta was 79.4% or classified as a high category with some related factors such as ethnicity, religion, discussion with partners prior to the HIV test, types of partners and knowledge on the partnersâ HIV status. Keywords: Women, HIV, Disclosure, Sexual Partner.